A Mantle Plume Connection for Alkaline Lamprophyres (Sannaites) from the Permian Tarim Large Igneous Province: Petrological, Geochemical and Isotopic Constraints. (19th January 2023) - Liu, Bingxiang; Zhang, Zhaochong; Giuliani, Andrea; Xie, Qiuhong; Kong, Weiliang; Wang, Changhong; Wei, Bowen; Ke, Shan; Santosh, M; Zhang, Bo; Zhang, Xingchao; Krmíček, Lukáš
Abstract: The origin of lamprophyres associated with large igneous provinces (LIPs) remains controversial, particularly whether they are derived by direct melting of mantle plumes, or from previously metasomatized domains in thermally perturbed subcontinental lithosphere. Here, we report the petrological and geochemical characteristics of a recently identified suite of alkaline lamprophyres (sannaites) that represent the final pulse of magmatism in the Permian Tarim LIP in NW China. The sannaites display porphyritic texture with phenocrysts of olivine, clinopyroxene, hornblende, phlogopite, and titanomagnetite in a groundmass of plagioclase, clinopyroxene, nepheline, hornblende, biotite, and titanomagnetite with minor pyrite and apatite. Carbonate ocelli and almost pure albite in the groundmass are interpreted to have crystallized from immiscible carbonate and hydrous fluids, respectively, produced by late-stage magmatic segregation. The rocks show low to moderate SiO2 (37.7–49.3 wt.%) and MgO (2.74–9.91 wt.%), together with high Fe2 O3 T (up to 22.7 wt.%) and alkali contents (up to 9.02 wt.% Na2 O + K2 O). They are characterized by high incompatible element abundances, especially a marked enrichment in large-ion lithophile elements (Rb and Ba) and light rare-earth elements (e.g. La and Ce) relative to P and high-field-strength elements (e.g. Ti). They show a relatively restricted range of δ 66 Zn values between 0.22‰ and 0.46‰ with an average of 0.37 ± 0.04‰ (2SE, n  = 10), which is marginally heavier than that of MORBs (0.27 ± 0.05‰). Their ( 87 Sr/ 86 Sr)t values range from 0.7035 to 0.7061, εNd (t) from −0.97 to +5.62, and δ 26 Mg from −0.36‰ to −0.17‰ ( n  = 8), the latter being consistent with those of global MORBs. Based on the correlation between Zn isotopes and TiO2 –FeO concentrations, we infer that the heavy Zn isotopes in some of the sannaites resulted from fractional crystallization of Fe–Ti oxide minerals. The whole rock geochemical features of these rocks (negative K anomalies and enrichment in large-ion lithophile elements) and rhyolite–MELTS simulations suggest that the primary magmas of the sannaites were derived from an amphibole-bearing enriched lithospheric mantle source. Metasomatism and related formation of amphibole-bearing metasomatized mantle may be linked to sublithospheric melts/fluids derived from the Tarim plume in the earlier stages of plume activity, rather than slab-derived fluids or carbonate melts as suggested in previous studies for other alkaline mantle-derived magmas. Partial melting may have been triggered by the thermal input from the Tarim plume during a later stage. This study suggests that exotic, alkali-rich magmas can be produced during the multi-stage evolution of large mantle plumes, involving complex cycles of lithospheric mantle metasomatism and later melting of previously enriched domains.